The Trend of the Bibliographical Output from Libyan Engineering Schools: A 30-Year Review From 1984-2013 - Bodalal, Awad; Mashite, Salah (International Journal of Statistics in Medical Research, 2018)
In this study, the research output from the major Libyan engineering schools was gathered and compared for the period of thirty years (from 1984 to 2013). The Elsevier database, Science Direct, was used to gather these publications and only engineering articles were included. A comparative analysis was performed on three levels; first a local comparison between the different faculties of engineering across Libya and secondly, a broader comparison between Libya and the neighboring METAL (Morocco, Egypt, Tunisia, Algeria and Libya) countries and finally, the third comparison was performed between Turkey and the METAL countries. In the local comparison, the output was normalized by the number of teaching staff while in the broader regional comparison, gross domestic product and population were used as standardization factors. When analyzing the research output of the Libyan engineering schools, it was observed that most publications came from Tripoli (47.1%, n=131) followed by Benghazi (25.9%, n=72), Misurata (4.1%, n=12) and Omar Al-Mukhtar (4.0%, n=11). However, when the number of staff members was taken into consideration, Benghazi University and Omar Al-Mukhtar University had higher research productivity levels than Tripoli University and Misurata University respectively. The regional comparison showed a clear difference between Libya and its neighbors, having the lowest output among them. Finally, it was found that across the three decades under study, Turkey produced more research than all the METAL countries combined. More attention needs to be paid to research and publications in Libyan engineering schools. A number of recommendations were made to help improve the publication rate in Libyan engineering faculties